1986
DOI: 10.1111/j.2042-7158.1986.tb04471.x
|View full text |Cite
|
Sign up to set email alerts
|

α-Tocopherol as agonist in hypoxia

Abstract: In hypoxia, but not normoxia, alpha-tocopherol (vitamin E) acts as an agonist in guinea-pig isolated colon, producing dose-dependent increases in contractile activity. This effect is mimicked by agents, vitamin K1 and phytol, which contain a structural similarity to the phytol side chain of alpha-tocopherol, but is antagonized by vitamin K3 which has a structure similar to the chromane ring of vitamin E. All of the agonist responses were blocked by atropine and potentiated by physostigmine but were unaffected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Phorbol-12,13-dibutyrate was purchased from Sigma-Aldrich Japan (Tokyo). DL- [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]ornithine hydrochloride (50-62 mCi/ mmol, 50 µCi/ml) and PDBU (10-20 Ci/mmol, 250 µCi/ ml) were obtained from Amersham Life Science (Tokyo). All chemicals were of the highest purity commercially available.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phorbol-12,13-dibutyrate was purchased from Sigma-Aldrich Japan (Tokyo). DL- [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]ornithine hydrochloride (50-62 mCi/ mmol, 50 µCi/ml) and PDBU (10-20 Ci/mmol, 250 µCi/ ml) were obtained from Amersham Life Science (Tokyo). All chemicals were of the highest purity commercially available.…”
Section: Methodsmentioning
confidence: 99%
“…9) Phytol (3,7,11,15-tetramethyl-2-hexadecen-1-ol), the fatty acid side chain of tocopherol, is a branched, longchain aliphatic alcohol contained in large quantities in plants and is a component of chlorophyll. In recent extensive studies, various cellular and biological effects of phytol have been demonstrated, such as its action as an agonist in hypoxia, 10) peroxisome proliferation in skin sebaceous glands 11) and in liver, 12) anti-inflammatory effects, 13) antispasmodic activity, 14) inhibition of efflux of creatine kinase, 15) and reduction of the duration of pentobarbital-induced sleep. 16) Clinically, phytanic acid, which is a derivative of phytol, is associated with Refsum's disease and a phytol-free diet can prevent the progression of that disease.…”
mentioning
confidence: 99%
“…Other experiments, using guinea pig colonic smooth muscle, indicate that vitamin K 1 , of a length similar to vitamin E, preserves the smooth muscle functionality during hypoxia [12].…”
Section: Introductionmentioning
confidence: 99%
“…However the chromane ring structure of the vitamin, Trolox, possessing the antioxidant capacity, was not protective and indeed antagonised the action of both vitamin E and phytol. Other experiments, using colonic smooth muscle, indicated that compounds with a phytyl side chain, phytol and vitamin K I , of similar length to vitamin E were active as agonists in hypoxia but compounds that had structural elements resembling the chroniane ring of the vitamin, vitamin K3 and Trolox, were antagonists of these hypoxic responses (Kelly 1986).…”
Section: Discussionmentioning
confidence: 99%